Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd009752
|View full text |Cite
|
Sign up to set email alerts
|

Red cell transfusion management for patients undergoing cardiac surgery for congenital heart disease

Abstract: Red cell transfusion management for patients undergoing cardiac surgery for congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
0
18
1
1
Order By: Relevance
“…This, however, remains a subject of debate, and a meta-analysis of 11 trials in congenital cardiac surgery could not accurately assess the impact of RBC transfusions on children undergoing cardiac surgery. 2 An efficient blood-sparing approach involves all of the contributors to the surgical performance: a meticulous surgical technique aimed to minimize blood loss, reduction of the priming volume, predefined transfusion trigger and monitoring of regional circulations for the detection of hypoxia, hemoconcentration and cell-salvage for retransfusion of autologuous RBC, and avoidance of unnecessary blood sampling.…”
Section: Blood Conse Rvationmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, remains a subject of debate, and a meta-analysis of 11 trials in congenital cardiac surgery could not accurately assess the impact of RBC transfusions on children undergoing cardiac surgery. 2 An efficient blood-sparing approach involves all of the contributors to the surgical performance: a meticulous surgical technique aimed to minimize blood loss, reduction of the priming volume, predefined transfusion trigger and monitoring of regional circulations for the detection of hypoxia, hemoconcentration and cell-salvage for retransfusion of autologuous RBC, and avoidance of unnecessary blood sampling.…”
Section: Blood Conse Rvationmentioning
confidence: 99%
“…Importantly, the mean perfusion pressure had poor correlation with the flow rate. To emphasize the importance of such a multimodal monitoring strategy, they showed that 14 of 34 patients had cerebral rSO2 of 95%, placing them at risk for cerebral hyperperfusion if the cerebral rSO 2 had been used alone to guide bypass flow. Finally, in order to minimize the need for deep hypothermia, surgeons are experimenting with moderately hypothermic splanchnic perfusion during reconstruction of the aortic arch.…”
mentioning
confidence: 99%
“…Although integral, there are risks associated with RBC transfusions that can translate into increased patient morbidity and mortality (1).…”
Section: Techniques and Technologies To Minimize Blood Transfusionmentioning
confidence: 99%
“…Transfusion medicine has improved vastly and the focus has shifted to adverse transfusion reactions such as acute lung injury, immunomodulation, and thrombotic complications (1)(2)(3). With focus increasing on these risks, centers have reevaluated RBC administration algorithms, especially for neonate and infant populations due to having a higher incidence of adverse reactions compared to older pediatric and adult patient populations (1,4). To reduce the potential exposure and risks associated with RBC transfusions, there are practices that can be put in place in the intraoperative period.…”
Section: Recent Innovations In Perfusion and Cardiopulmonary Bypass Fmentioning
confidence: 99%
“…What are optimal RBC transfusion strategies for anemia not related to acute hemorrhage in children who undergo surgery? [49][50][51] Data supporting RBC transfusion strategies for critically ill children undergoing surgical procedures (e.g., traumatic brain injury, congenital heart disease, liver transplant, spinal surgery) are limited, mainly retrospective, and single center. These surgical procedures are conducted in medically fragile patients whose complicated physiology, including altered vasomotor autonomic regulation, existing coagulopathy, myocardial depression, and/or varying degree of desaturation, may impair adaptive physiologic responses to shock (oxygen debt).…”
Section: Devices and Surgerymentioning
confidence: 99%